Being and becoming : embodiment and experience among the Orang Rimba of Sumatra - Elkholy, Ramsey (Berghahn Books, 2016)
For the Orang Rimba of Sumatra ' and tropical foragers in general ' life in the forest engenders a kind of 'connectedness' that is contingent not only on harmonious relations between people, but also between people and the non-human environment, including those supernatural agencies of the forest that people depend on for their spiritual and emotional wellbeing. Exploring this world, anthropologist Ramsey Elkholy treats embodied action and perception as the basis of shared experience and shows how various forms of embodied experience constitute the very foundations of human culture. In a unique methodological contribution, Elkholy adopts a set of body-centered approaches that reflect and capture the day-to-day, moment-to-moment ways in which people engage with the world. Being and Becoming is an important contribution to phenomenological anthropology, hunter-gatherer studies, and to Southeast Asian ethnography more generally.